2021
DOI: 10.21203/rs.3.rs-173554/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Role of Opioids in Cancer Response to Immunotherapy

Abstract: Background: The response to immunotherapy can be impaired by several factors including external intervention such as drug interactions with immune system. We aimed to examine the immunomodulatory action of opioids, since immune cells express opioid receptors able to negatively influence their activities.Methods: This observational, multicenter, retrospective study, recruited patients with different metastatic solid tumors, who have received immunotherapy between September 2014 and September 2019. Immunotherapy… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…The study by Wang mentioned that differences in RT techniques or factions also play a role in shaping IDO1 activity and immune status (14). A higher kyn/trp ratio could predict resistance to anti-PD-1 treatment in NSCLC patients (11,35). Clinical trials are ongoing to explore the possibility of concurre nt immunotherapy and radiotherapy (KEYLYNK-012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study by Wang mentioned that differences in RT techniques or factions also play a role in shaping IDO1 activity and immune status (14). A higher kyn/trp ratio could predict resistance to anti-PD-1 treatment in NSCLC patients (11,35). Clinical trials are ongoing to explore the possibility of concurre nt immunotherapy and radiotherapy (KEYLYNK-012).…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that increased IDO1 activity is detected in NSCLC patients and is associated with poorer survival (10). IDO1 activity also predicts the efficacy of chemotherapy or immunotherapy in lung cancer patients (11,12). Kong is the first to report that reduced levels of Kyn : Trp ratios were observed during RT in stage III inoperable NSCLC patients but restored 3 months after RT completion.…”
Section: Introductionmentioning
confidence: 99%